MULTIKULTURALISME DALAM PENDIDIKAN ISLAM - Fitri Nur Hidayat (Journal Multicultural of Islamic Education, 2023)
Multicultural education emerged as part of a response to the phenomenon of ethnic, social and cultural conflict which often arises in multicultural societies. Multiculturalism is an understanding of the acceptance of pluralism in society so as to avoid horizontal conflict in society. The design of multicultural education in the book written by Kasinyo Harto entitled Multicultural-Based Islamic Religious Education Development Model emphasizes the cultivation of a method of living that is respectful, sincere and tolerant of cultural diversity that lives in the midst of a pluralistic society. This research uses a type of library research. The source of research data is Kasinyo Harto's book entitled Multicultural-Based Islamic Religious Education Development Model. The data collection technique was carried out using documentation techniques and descriptive analysis was chosen to describe and analyze the data obtained simultaneously. Multiculturalism in Islamic Religious Education in schools is teaching the Islamic religion to students openly and dialogically so that all students have the same opportunities and do not discredit other religions that are not the same as the religion of the religious teacher.